2016
DOI: 10.21037/jtd.2016.03.13
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the single-lumen endotracheal tube and double-lumen endobronchial tube used in minimally invasive cardiac surgery for the fast track protocol

Abstract: Background: Minimally invasive cardiac surgery (MICS) has been more commonly performed due to the reduced amount of bleeding and transfusion and length of hospital stay. We investigated the feasibility of performing MICS using single-lumen endotracheal tube (SLT). Methods: We conducted a retrospective review of clinical data of 112 patients who underwent MICS between July 2012 and March 2015. The patients underwent MICS using a SLT or a double lumen endotracheal tube (DLT). The duration of intensive care unit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Postoperatively, ventilation time and the lengths of ICU and hospital stay were significantly shorter in the SL group in our study. Kim et al 22 showed no difference in these parameters between patients with SL and DL endotracheal intubation. In most reports on robotic surgery, patients are extubated immediately using the fast track protocol and prolonged intubation is uncommon 2‐11,16,19 .…”
Section: Commentsmentioning
confidence: 94%
See 4 more Smart Citations
“…Postoperatively, ventilation time and the lengths of ICU and hospital stay were significantly shorter in the SL group in our study. Kim et al 22 showed no difference in these parameters between patients with SL and DL endotracheal intubation. In most reports on robotic surgery, patients are extubated immediately using the fast track protocol and prolonged intubation is uncommon 2‐11,16,19 .…”
Section: Commentsmentioning
confidence: 94%
“…Currently, DL endotracheal intubation with lung isolation is the standard for robotic cardiac surgery in high volume robotic cardiac centers 1‐3,10,11,15‐19 . This approach has been applied in video‐assisted cardiothoracic surgery to ensure lung exclusion 20‐26 . However, proper placement of DL endotracheal tubes or bronchial blockers for lung isolation is a complex procedure, requires experienced anesthesiologists and carries potential hazards even in experienced hands 12‐15 .…”
Section: Commentsmentioning
confidence: 99%
See 3 more Smart Citations